Quantifying Dissolved Lignin Phenols in the Albemarle–Pamlico Estuarine System and Coastal North Carolina following the 2018 Hurricane Florence - Ferris, Kathleen J (East Carolina University, 2022)
The global carbon cycle (GCC) involves the exchange and transformation of carbon across the ocean, atmosphere, and terrestrial reservoirs. It consists of a positive feedback loop involving dissolved organic matter in natural waters, greenhouse gases, and global warming. Extreme weather events such as hurricanes can accelerate this feedback loop by rapidly increasing the flux of organic matter to coastal systems. The 2018 Atlantic Ocean hurricane season with its numerous and large storms, adversely impacted North Carolina, USA. One of the largest storms of the season was Hurricane Florence, which released over 900 mm of precipitation across the state causing runoff, erosion, and flooding of terrestrial organic material (TOM). This study quantified dissolved lignin, a bulky biopolymer that is found within the cell wall of vascular land plants, as a biomarker of TOM influx into the Albemarle-Pamlico Estuarine System (APES) and coastal ocean of North Carolina. Water samples were collected in October and November of 2018 which represented hurricane-influenced samples. In contrast, water samples collected in July 2019 represented non-storm conditions. All water samples were filtered at 0.2 [micro]m to isolate and analyze the truly dissolved phase. A subset of each filtered water sample were sent to the NC State Stable Isotope Laboratory for bulk dissolved organic carbon ([delta]¹³CDOC) analysis, to help identify its source. Additionally, an existing method for quantifying dissolved lignin, originally designed for liquid chromatography, was modified to allow low volume quantification of dissolved lignin via gas chromatography-mass spectrometry (GC-MS). Dissolved lignin was quantified in 3 replicates each of standard reference materials (SRM): NIST SRM 1944 (New York/ New Jersey Waterway Sediment), NIST SRM 8704 (Buffalo River Sediment), and Aldrich Humic Acid. Total dissolved lignin was determined to be (160.12 [plus-minus] 12.84 [mu]g L⁻1), (129.87 [plus-minus] 6.30 [mu]g L⁻1), and (1,124.34 [plus-minus] 33.21 [mu]g L⁻1), in SRM 1944, 8704, and Aldrich Humic Acid, respectively. There are no existing measurements of dissolved lignin in these reference materials in the literature. Thus, the low standard deviation and high precision across replicates suggested that the method that was developed was precise, and thus applicable to natural water samples. Water samples collected from the APES and coastal ocean system in 2018 yielded overall higher concentrations of total dissolved lignin (2.84 [plus-minus] 1.84 [mu]g L⁻1) than those collected during 2019 (0.67 [plus-minus] 0.67 [mu]g L⁻1). The estuary had, on average, higher dissolved lignin concentrations in both 2018 and 2019 than that of the coastal ocean waters. Lignin interclass ratios of syringyl to vanillyl monomers (S/V; angiosperm vs gymnosperm) and C/V (cinnamyl to vanillyl; grasses versus woods) were calculated and used to provide insight on TOM sources. Average S/V values were 1.96 [plus-minus] 2.71 and 2.10 [plus-minus] 2.86, in 2018 and 2019 respectively. Average C/V were 1.54 [plus-minus] 1.80 and 2.33 [plus-minus] 2.94, in 2018 and 2019 respectively. Degradation of TOM was determined using acid to aldehyde ratio of vanillyl and syringyl monomers; [Ad/Al]V and [Ad/Al]S. Ratios of [Ad/Al]V were 8.11 [plus-minus] 15.93 and 3.69 [plus-minus] 4.58, in 2018 and 2019 respectively. Similarly, ratios of [Ad/Al]S were 11.11 [plus-minus] 26.18 and 8.26 [plus-minus] 10.98, in 2018 and 2019 respectively. These ratios in conjunction with [delta]¹³CDOC which was -27.9 [plus-minus] 1.7 and -26.6 [plus-minus] 0.9 % for 2018 and 2019 respectively, suggested that the dissolved lignin samples of 2018 were generally derived from fresh angiosperm and gymnosperm tissues, while 2019 samples were much more degraded in comparison but had similar plant tissue sources. The overarching results from this study indicate that Hurricane Florence directly increased the concentration of terrestrially derived dissolved lignin to the APES and coastal North Carolina by approximately 76.4 % via erosion, flooding, and runoff. Such rapid pulses of TOM have been shown in other coastal ecosystems to increase regional concentrations of CO2(g), a greenhouse gas. Although not directly quantified in this study, a similar effect likely occurred in coastal NC because of the 2018 hurricane season.
Keywords: Geology; Biomarker; Carbon cycle (Biogeochemistry)--North Carolina--Albemarle Sound; Hurricane Florence, 2018; Carbon cycle (Biogeochemistry)--North Carolina--Pamlico Sound; Estuarine ecology--North Carolina--Albemarle Sound; Estuarine ecology--North Carolina--Pamlico Sound; Lignin